2021
DOI: 10.3389/fonc.2021.764076
|View full text |Cite
|
Sign up to set email alerts
|

Albumin-To-Alkaline Phosphatase Ratio as a Novel and Promising Prognostic Biomarker in Patients Undergoing Esophagectomy for Carcinoma: A Propensity Score Matching Study

Abstract: BackgroundAlbumin-to-alkaline phosphatase ratio (AAPR) has been reported as a novel prognostic predictor for numerous solid tumors. We aimed to assess the prognostic role of preoperative AAPR in surgically resectable esophageal squamous cell carcinoma (ESCC) by a propensity score matching (PSM) analysis with predictive nomograms.MethodsOur study was conducted in a single-center prospective database between June 2009 and December 2012. Kaplan-Meier analysis was used to distinguish the difference in survival out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Additionally, a study conducted by Liu et al demonstrated that APAR was independently associated with mortality in patients with sepsis [14]. Moreover, higher APAR levels were independently associated to increased cancer mortality as reported, including lung cancer [7,8,11], hepatocellular carcinoma [6], pancreatic ductal adenocarcinoma [9,20], nasopharyngeal carcinoma [12], urothelial carcinoma [13], and some other types [22][23][24][25][26][27][28][29]. However, there is limited evidence from large-scale general populations, making direct comparisons with our study challenging due to the heterogeneity of the study populations.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a study conducted by Liu et al demonstrated that APAR was independently associated with mortality in patients with sepsis [14]. Moreover, higher APAR levels were independently associated to increased cancer mortality as reported, including lung cancer [7,8,11], hepatocellular carcinoma [6], pancreatic ductal adenocarcinoma [9,20], nasopharyngeal carcinoma [12], urothelial carcinoma [13], and some other types [22][23][24][25][26][27][28][29]. However, there is limited evidence from large-scale general populations, making direct comparisons with our study challenging due to the heterogeneity of the study populations.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that cancer progression is affected by both cancer cells and the immune system. First, albumin can protect cells against tumorigenesis by helping stabilize cell growth and DNA replication ( 25 ) and is an independent prognostic factor in ESCC patients ( 26 ). Second, lymphocytes inhibit tumor cell proliferation and invasion through cytokine-mediated cytotoxicity ( 27 ), in which neutrophils can promote tumor angiogenesis and metastasis, and promote tumor progression by inhibiting T cells ( 28 ), with an increase in neutrophils associated with poor cancer prognosis ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…PSM is also widely used to assess the effectiveness of a certain treatment on outcomes. [29][30][31][32] Following PSM of the RT and non-RT groups, none of the possible confounding factors, such as lesion location, NLR (>8.9 or ≤8.9), and tumor differentiation, differed significantly. Both PFS and OS in the PSM cohort were significantly longer…”
Section: Discussionmentioning
confidence: 99%